Reestructuración técnico administrativa de industrias Tornometal JR S.A.S. (2017)
In the following project a technical administrative restructuring is done of agroindustrial machinery makers, Industrias Tornometal Jr SAS. With the purpose of identifying the present state of the company was made an internal and external diagnosis PESTAL, through engineering tools as Ishikawa chart, Cámara de Comercio de Bogotá survey, was possible identified improvement strategies. Afterwards was development a technical study composed by an analysis of times and movements, methods, capacity analysis, demand analysis, 5`S, it brought results time and money savings for the company.